Calcium Phosphate Carrying Simvastatin Enhances Bone Regeneration: A Systematic Review - Cruz,Rebecca (2020)
Abstract Several studies have aimed to develop alternative therapeutic biomaterials for bone repair. The purpose of this systematic review was to evaluate how statins carried by calcium phosphate affect the formation and regeneration of bone tissue in animal models when compared to other biomaterials or spontaneous healing. This systematic review followed the recommendations of the Cochrane Handbook for Systematic Reviews of Interventions, the PRISMA guidelines, and the Preclinical Systematic Review & Meta-analysis Facility (SyRF). The protocol of this systematic review was registered in PROSPERO (CRD42018091112) and in CAMARADES. In addition, ARRIVE checklists were followed in order to increase the quality and transparency of the search. An electronic search was performed using the MEDLINE/PubMed, Scopus, SciELO, and PROSPERO library databases. The authors used a specific search strategy for each database, and they also conducted a search in the grey literature and cross-references. The eligibility criteria were animal studies, which evaluated bone repair treated with calcium phosphate as a simvastatin carrier. The selection process yielded 8 studies from the 657 retrieved. All manuscripts concluded that locally applied simvastatin carried by calcium phosphate is biocompatible, enhanced bone repair and induced statistically greater bone formation than cloth or calcium phosphate alone. In conclusion, the pertinent pre-clinical studies evidenced the calcium phosphate biocompatibility and its effectiveness in delivering SIM to improve the repair of bone defects. So, clinical trials are encouraged to investigate the impact of SIM associated with calcium phosphate bone graft in repairing bone defect in humans.